KEPEMIMPINAN TRANSFORMASIONAL DAN PEMBERDAYAAN DI LEMBAGA PENDIDIKAN ISLAM - Achmad Faisol Syaifullah; Achmad Patoni; Binti Maunah (ISLAMIC EDUCATION MANAGEMENT STUDY PROGRAM, 2024)
Empowerment is considered a progressive means to enhance employees' competence within an organization. However, empowerment may not materialize within an organization without good leadership. Therefore, transformational leadership becomes the solution to empower employees so that organizational goals can be achieved. This study aims to elucidate the concept of transformational leadership and its influence on empowerment in Islamic educational institutions. The results of the study indicate the close relationship between leadership and empowerment. This relationship is manifested in three levels of empowerment: encouraging employees to become more active, involving employees in determining methods or creating innovations, and entrusting employees to make decisions.